PENGARUH DISIPLIN, MOTIVASI, DAN LINGKUNGAN KERJA TERHADAP KINERJA APARATUR SIPIL NEGARA (ASN) PADA DISPERINDAG KABUPATEN SITUBONDO FAKULTAS EKONOMI UNIVERSITAS ABDURACHMAN SALEH SITUBONDO - Maya, Maya (Growth, 2024)
This study aims (1) to determine the effect of discipline, motivation and work environment have a partially influence the performance of the state civil service (2) to determine the effect of discipline, motivation and work environment simultaneously influence the performance of the state civil service (3) to find out among the affects of the state civil appratus. The method used in this study is a quantitative method. The result of the study is multiple linear regression equation Y = -3,474E-16 + (-0,070) X1 + 0,201 X2 + 0,369 X3 + e. partially the discipline does not have a significant positive effect with a value of -0,699, ttabel of 1,992, motivation no effect significant positive with a value of 1,769 of 1,992, work invironment has a significant positive effect with a value of 3,257of 1,992. Simultaneously discipline, motivation and work environment have a partially influence the performance of the state civil service with a value of 8,291, 2,73. The most dominant variable in this study is work environment with a value of 3,257.